2013
DOI: 10.1002/ardp.201300189
|View full text |Cite
|
Sign up to set email alerts
|

N‐{[2‐(4‐Phenyl‐piperazin‐1‐yl)‐ethyl]‐phenyl}‐arylamides with Dopamine D2 and 5‐Hydroxytryptamine 5HT1A Activity: Synthesis, Testing, and Molecular Modeling

Abstract: The ratio of affinities toward the dopamine D₂ and the 5-hydroxytryptamine 5-HT(1A) receptors is one of the important parameters that determine the efficiency of antipsychotic drugs. Here, we present the synthesis of ortho-, meta-, and para-N-{[2-(4-phenyl-piperazin-1-yl)-ethyl]-phenyl}-arylamides and their structure-activity relationship studies on dopamine D₂ and 5-hydroxytryptamine 5-HT(1A) receptors. It was shown that the biological activity of the described ligands strongly depends on their topology as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the present study, a somewhat better efficiency of 6b , reflected in the later onset and lower maximal disease score (Table ), correlated with its higher binding affinities for D 2 ( K i 1400 and 71.6 nM for 6a and 6b , respectively) and 5‐HT 1A receptors ( K i 304.9 and 2.4 nM) (Sukalovic et al . ). Therefore, it is possible that dopamine/serotonine receptor binding in arylpiperazine‐mediated beneficial effects in neuroinflammation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the present study, a somewhat better efficiency of 6b , reflected in the later onset and lower maximal disease score (Table ), correlated with its higher binding affinities for D 2 ( K i 1400 and 71.6 nM for 6a and 6b , respectively) and 5‐HT 1A receptors ( K i 304.9 and 2.4 nM) (Sukalovic et al . ). Therefore, it is possible that dopamine/serotonine receptor binding in arylpiperazine‐mediated beneficial effects in neuroinflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, it should be noted that the arylpiperazines investigated in the present study act as D 2 and 5‐HT 1A receptor ligands (Sukalovic et al . ), displaying partial D 2 agonist activity (Tovilovic et al ., unpublished results). In the present study, a somewhat better efficiency of 6b , reflected in the later onset and lower maximal disease score (Table ), correlated with its higher binding affinities for D 2 ( K i 1400 and 71.6 nM for 6a and 6b , respectively) and 5‐HT 1A receptors ( K i 304.9 and 2.4 nM) (Sukalovic et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous publications, we demonstrated that N ‐{[2‐(4‐phenyl‐piperazin‐1‐yl)‐ethyl]‐phenyl}‐arylamides of the structural formula shown in Scheme provides neuroprotection in vitro and in vivo through a stabilizing mitochondria function but not through their dopaminergic and serotonergic properties . In cell‐based model of nitric oxide‐mediated neurotoxicity, their protective effect was associated with the inhibition of proapoptotic (JNK, ERK, and AMPK) and activation of antiapoptotic (Akt) signaling pathways .…”
Section: Introductionmentioning
confidence: 96%
“…In our previous publication , we showed that among N ‐arylpiperazines examined, the compounds with more flexible molecules expressed higher D 2 DAR affinity than rigid ones. This paper presents a further examination of the impact of molecule rigidity and functionalization of N ‐arylpiperazines on their D 2 DAR affinity.…”
Section: Introductionmentioning
confidence: 99%